2021
DOI: 10.3390/healthcare9080949
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation in the Treatment of Alzheimer’s Disease and Other Dementias

Abstract: Dementia is a debilitating impairment of cognitive functions that affects millions of people worldwide. There are several diseases belonging to the dementia spectrum, most prominently Alzheimer’s disease (AD), vascular dementia (VD), Lewy body dementia (LBD) and frontotemporal dementia (FTD). Repetitive transcranial magnetic stimulation (rTMS) is a safe, non-invasive form of brain stimulation that utilizes a magnetic coil to generate an electrical field and induce numerous changes in the brain. It is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…The application of rTMS in earlier disease stages is another issue that needs to be discussed. For instance, regarding AD, a common degenerative disorder combined with dementia, the excitant literature shows that patients in earlier stages had responded better after treatment with rTMS [ 32 , 62 , 63 ]. This phenomenon could be explained from the smaller degree of brain atrophy, contributing to better responsiveness to rTMS [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of rTMS in earlier disease stages is another issue that needs to be discussed. For instance, regarding AD, a common degenerative disorder combined with dementia, the excitant literature shows that patients in earlier stages had responded better after treatment with rTMS [ 32 , 62 , 63 ]. This phenomenon could be explained from the smaller degree of brain atrophy, contributing to better responsiveness to rTMS [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…rTMS has been considered to be a therapeutic option for many pathologies, such as depression, migraine, and epilepsy [ 29 31 ], and even neurodegenerative conditions with cognitive sequelae, such as Alzheimer's disease [ 32 ]. In addition, rTMS has been extensively studied in PD, showing positive effects in motor and nonmotor symptoms and in therapy complications [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…LTP-like plasticity is reduced in both presymptomatic and symptomatic FTD ( 138 ). Studies investigating TMS combined with cognitive training have shown promising results, suggesting a synergistic effect enhancing the benefits of each intervention ( 140 ).…”
Section: Aging and Neurodegenerative Disordersmentioning
confidence: 99%
“…Aloizou et al reviewed the available studies that have used repetitive transcranial magnetic stimulation (rTMS) for the treatment of the most common types of dementia [17]. It has been argued that the application of this method, either alone or in combination with pharmaceutical therapy and cognitive training, appears to produce positive results in terms of improving cognitive functions.…”
mentioning
confidence: 99%